Impact of Smoking on Women During the Covid-19 Pandemic - Mihaltan, Florin Dumitru; Rajnoveanu, Armand-Gabriel; Rajnoveanu, Ruxandra-Mioara (Frontiers in Medicine, 2021)
The coronavirus disease 2019 (COVID-19) brought in 2020 an important challenge for health care systems and authorities. Smoking and its influence on this disease remain, after months of the pandemic, one of the debatable risk factors. From the literature point of view, the focus of most articles is on smoking as a possible general risk factor for all analyzed populations. Women tend to represent a more significant population in exposed occupations. In our mini-review, we try to dig deeper, looking for gender-related health effects of smoking in this pandemic context, its effects on the infection with this novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), on illness severity, and on the rate of hospitalization and mortality. Despite the fact that the male gender is reported in many articles as a predictor of a poor outcome, we suggest that further research is needed to confirm or deny these relationships. Moreover, studies focusing specifically on women in these study populations are required.